Analysis of influencing factors in emergency management based on an integrated methodology. (October 2019) - Liu, Xiaodi; Wang, Zengwen; Zhang, Shitao; Liu, Jiashu
Various emergencies are happening frequently in recent years, causing great loss of life and property. Therefore, it has become imperative to improve emergency management. Considering that the performance of emergency management could be affected by many different factors, it is hard to improve all the factors under the condition of limited resources. One approach that works well is to optimize the key factors that affect emergency management. To this end, an integrated method based on fuzzy cognitive map (FCM) and Pearson's product-moment correlation coefficient is presented in this article to determine the critical risk factors in emergency management. First, the causal relationships between the risk factors influencing emergency management are determined according to expert opinions. To verify if the survey results from experts are reliable, an item-average correlation test based on Pearson's product-moment correlation coefficient is performed. Then, two scenarios are designed and the FCM method is utilized to identifying the critical risk factors of emergency management. Finally, five critical factors are figured out, and the efficiency of emergency management could be enhanced by optimizing these five factors. In addition, a comparative analysis is also conducted to validate the advantages of the proposed method.